Liquidity Preference as Behavior Towards Risk - Tobin, J. (Review of Economic Studies, 1958)
Journal Article Liquidity Preference as Behavior Towards Risk Get access J. Tobin J. Tobin New Haven, Conn. U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 2, February 1958, Pages 65–86, https://doi.org/10.2307/2296205 Published: 01 February 1958